Availability, accessibility and utilization of Pacific island demographic data - Issues of data quality and user relevance - Gerald Haberkorn; Arthur Jorari (Asia-Pacific Population Journal, 2007)
The Pacific region is comprised of 22 island countries and territories - featuring some 7,500 islands of which around 500 are inhabited-spread over an area of 30 million square kilometres and stretching from the Northern Marianas Islands in the north-west Pacific Ocean to Pitcairn in the south-east. Representing an enormous diversity in physical geography and culture, languages and socio-political organization, size and resources endowment, some countries and areas such as Nauru and Niue, consist just of one coral island, whereas others, like Papua New Guinea and the Federated States of Micronesia comprise literally of hundreds of islands. Melanesia comprise large, mountainous and mainly volcanic islands, endowed with natural resources, rich soil and an abundant marine life. Micronesia and Polynesia, by contrast, comprise of much smaller islands and their natural resources are limited to the ocean; they mostly comprise of small atolls with poor soil, with elevations usually between one and two metres (Kiribati, Marshall Islands, Tokelau and Tuvalu). There are also some islands of volcanic origin with more fertile lands (such as Samoa, Tonga, the Federated States of Micronesia and the Cook Islands).